Design of Wireless Automatic Synchronization for the Low-Frequency Coded Ground Penetrating Radar - Zhenghuan Xia; Qunying Zhang; Shengbo Ye; Zhiwu Xu; Jie Chen; Guangyou Fang; Hejun Yin (Journal of Electrical and Computer Engineering)
Low-frequency coded ground penetrating radar (GPR) with a pair of wire dipole antennas has some advantages for deep detection. Due to the large distance between the two antennas, the synchronization design is a major challenge of implementing the GPR system. This paper proposes a simple and stable wireless automatic synchronization method based on our developed GPR system, which does not need any synchronization chips or modules and reduces the cost of the hardware system. The transmitter omits the synchronization preamble and pseudorandom binary sequence (PRBS) at an appropriate time interval, while receiver automatically estimates the synchronization time and receives the returned signal from the underground targets. All the processes are performed in a single FPGA. The performance of the proposed synchronization method is validated with experiment.